The Effect of Online Learning using Google Classroom on The Story Writing Skills of the Fifth Grade Student Of YPS Singkole Primary School East Luwu District - Amalia Kusmalasari; Widya Karmila Sari Achmad; Rohana Rohana (International Journal of Elementary School Teacher, 2021)
This study is pre-experimental that aimed to know the effect of Online Learning Google Classroom Based on the story writing skills of the Fifth Grade Students YPS Singkole Elementary School East Luwu District. The independent variable in this study is Online Learning Google Classroom Based and the Fifth Grade Students YPS Singkole Elementary School East Luwu District that consist of 28 students. The research data were obtained by giving story writing tests on learning the theme of My living place, sub theme 2: the diversity of living things in my environtment with pre test and post test. The data analysis technique is descriptive statistical analysis and inferential statistical analysis. Based on the results of inferential statistical analysis, the obtained Wilcoxon test was for 0.000 less than 0.05. It can be concluded that Online Learning Google Classroom Based has a significant effect on the story writing skills of the Fifth Grade Students YPS Singkole Elementary School East Luwu District.